Pengaruh Kunyit dalam Pengelolaan Stres Oksidatif dan Implikasinya terhadap TNF Alfa dan Kesehatan Sel - Made Rendra Wisnu Rahasbistara (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This article aims to examine the relationship between turmeric consumption and the management of oxidative stress and its effects on TNF-α expression and cellular health, in order to provide a scientific understanding of turmeric's potential as a therapeutic agent in the prevention and treatment of various degenerative diseases through antioxidant and anti-inflammatory mechanisms. This study uses a qualitative approach with a literature review method to examine the effect of turmeric, specifically curcumin, in managing oxidative stress and TNF-α expression related to cellular health. Data were collected through a search of scientific literature from trusted sources such as PubMed, Scopus, and Google Scholar, with a focus on relevant and credible publications. The analysis was conducted descriptively and analytically to synthesize new understanding of curcumin's role as a natural agent in cell protection and recovery. The results show that curcumin in turmeric has a positive impact on cellular health by increasing the body's antioxidant activity. Curcumin is also effective in reducing inflammation-causing compounds, thereby helping to relieve inflammatory symptoms. These effects accelerate cell regeneration, strengthen connective tissue, and accelerate wound healing. Thus, curcumin has great potential as a natural agent in the prevention and treatment of various disorders related to oxidative stress and chronic inflammation.